Case Report: Direct anterior approach with surgical hip dislocation for management of juvenile femoral head chondroblastoma: a case series and systematic review of the literature - Yang, Xiujiang; Luo, Xiaolin; Li, Xiudong; Pang, Ke; Zou, Yuanhan; Ding, Xiaofei; Liao, Shijie (Frontiers in Pediatrics, 2026)
BackgroundFemoral head chondroblastoma is a rare benign tumor in adolescents (10–20 years). Traditional surgeries face difficulties like poor exposure, high trauma, and risks of physeal injury/avascular necrosis (AVN). The DAA-SHD approach (no greater trochanteric osteotomy) is proposed for direct tumor resection, vascular preservation, and articular cartilage repair.MethodsA literature review (2005–2025) on adolescent femoral head chondroblastoma was conducted. Retrospective analysis of 4 cases (2014–2025) treated with supine DAA-SHD (same senior surgeon) autologous iliac bone grafting. Hip function was assessed via MSTS scale.ResultsMean follow-up: 64.75 months (9–124 months). All 4 cases had excellent/good MSTS scores (25–29 points). Imaging showed satisfactory bone graft healing; no AVN, recurrence, or limp/pain occurred.ConclusionSupine DAA-SHD (no trochanteric osteotomy) is effective for adolescent femoral head chondroblastoma, enabling complete resection, anatomical reconstruction, and vascular protection. It enriches pediatric hip tumor treatment options but needs validation via large-scale prospective studies.